1989
DOI: 10.1093/ajcn/49.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Diets containing high amylose vs amylopectin starch: effects on metabolic variables in human subjects

Abstract: Twelve men consumed a diet containing 34% of calories as 70% amylose or amylopectin starch to determine if the structure of starch could influence metabolic factors associated with abnormal states. Each starch was fed to subjects for 5 wk in a crossover design. No significant differences were observed in glucose or insulin levels when a glucose tolerance was given after 4 wk on each starch. However, glucose and insulin responses were significantly lower when a meal containing amylose compared with amylopectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
1
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(109 citation statements)
references
References 35 publications
5
99
1
3
Order By: Relevance
“…The lowering of hyperglycaemic effects previously found with high amylose food was not always consistent and may have depended on the nature and amount of amylose added , the technological process applied to food and therefore the physico-chemical characteristics of starch (Behall et al, 1989;van Amelsvoort & Weststrate, 1992;Granfeldt et al, 1995;Heijnen et al, 1995). In our study, the substitution of amylose-rich maize starch for 40% of white wheat¯our led to an increase in the resistant starch content of HAWB (14% of DM) which involved a decrease of the extent of bioavailability of starch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowering of hyperglycaemic effects previously found with high amylose food was not always consistent and may have depended on the nature and amount of amylose added , the technological process applied to food and therefore the physico-chemical characteristics of starch (Behall et al, 1989;van Amelsvoort & Weststrate, 1992;Granfeldt et al, 1995;Heijnen et al, 1995). In our study, the substitution of amylose-rich maize starch for 40% of white wheat¯our led to an increase in the resistant starch content of HAWB (14% of DM) which involved a decrease of the extent of bioavailability of starch.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant starch in crystalline form has been generated by raw starch granules, retrograded amylose, or a mixed structure (Englyst et al, 1992). Some studies have attempted to capitalise on the functional properties of amylose for the generation of resistant starch by adding high amylose maize starch in bakery products (Behall et al, 1989;Weststrate & van Amelsvoort, 1993;Heijnen et al, 1995;Granfeldt et al, 1995). Moreover, inconsistent results are obtained on the effect of high amylose content in various kinds of bread on postprandial glucose and insulin (Weststrate & van Amelsvoort, 1993;Granfeldt et al, 1995;Heijnen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foods that are rich in fiber slows down the absorption of sugar, which results in lowering of bad cholesterol and improving blood sugar levels in diabetes and may also protect against cancer (Augustin et al 2001;Satya et al 2011). The amylose content was highest in T5, followed by T4, T3, T2 (Behall et al 1989;Hoebler et al 1999). Leeman et al (2008) suggested that amylose is prone to react with lipids to form amylose-lipid complexes thus reduces the rate of amylolysis and results in lower glycemic responses and GI values.…”
Section: Nutrient Analysismentioning
confidence: 99%
“…Another hypothesis to explain the effects of this starch on plasma lipids concerns its effect on insulin and glucagon levels, since the intestinal hydrolysis of amylose-rich starch and therefore the glucose release are slow. Indeed, glucose and insulin responses were decreased when the amylose content of rice starch [22] and cornstarch [23,24] was increased. Moreover O'Dea et al showed that the insulin response after a meal was closely related to the starch digestibility tested in vitro [25].…”
Section: Discussionmentioning
confidence: 99%